(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The spatial distribution of industrial enterprises is closely related to the development of transport systems that unite them into a single regional complex. Sustainable operation of transport systems is a guarantee of a single space, free movement of goods and services, improvement of conditions and living standards of the region’s population. The transport system ensures the territorial integrity of the region and the unity of the economic space based on the movement of passengers and goods, linking the region’s enterprises into a single complex and ensuring the continuity of the processes of development of productive forces. The existing approaches to assessing this indicator are of a complex nature, but they do not take into account the influence of a number of factors associated with the peculiarities of the spatial distribution of the population of certain, for example, northern territories. The lack of objective statistical data does not allow researchers to conduct a comprehensive assessment of transport accessibility. Despite this, many authors are considering the possibility of measuring transport accessibility based on taking into account the costs of movement. The authors of the article propose to use this approach, improving it by refining the formula for the cost of travel time, which makes it possible to objectively compare the transport accessibility of various settlements to the regional center. Thus, this study is devoted to the study of transport accessibility as a leading factor in the development of the regional economy